Development of Independent Curriculum IPAS Teaching Materials Using a Project-Based Learning Approach Assisted with the Kvisoft Flipbook Maker Application to Increase the Learning Motivation of Class IV Primary School Students - Nurhidayati; Firman; Yeni Erita; Daharnis (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop IPAS teaching materials using a Project Learning approach assisted by the Kvisoft Flipbook Maker application to increase the learning motivation of fourth-grade elementary school students. This type of research is Research and Development (R&D) research using a 4-D development model consisting of four stages: analysis, design, development, and implementation. The media developed is science and technology teaching materials using a Project Learning approach assisted by the Kvisoft Flipbook Maker application to increase the learning motivation of fourth-grade elementary school students. The results of the research show that: the validity test of IPAS teaching materials obtained an overall validity value of 91.80 % in the very valid category; The teacher's practicality results were 93.30 % in the convenient category and the students' practicality results obtained a percentage of 93.50 % in the convenient category; the effectiveness used in increasing the learning motivation of fourth-grade elementary school students received an N-gain value of 0.73 in the high category. From the results of this research, it can be concluded that the IPAS teaching materials using the Project Based Learning approach assisted by the Kvisoft Flipbook Maker application to increase the learning motivation of fourth-grade elementary school students are valid, practical and effective and can increase the learning motivation of fourth-grade elementary school students.